Беги: [роман] / Лидия Давыдова - Давыдова Лидия Евгеньевна (Эксмо, 2022)
На обложке: Выбор - это твоя сила Экземпляры: ЦБ (20230511) / Инвентарный номер: 58633 / Цена: 297.14 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Д 13 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44